Self-image and self-esteem of ostomized patients - Pigatto, Bruno; Viegas, Graziela Lenz; Cebulski, Jenifer Nascimento da Silva; Lima , Juliana da Silva; Souza, Luciana Pereira Tarragô de; Nascimento, Patrícia do; Mari, Sídia de (Seven Editora, 2023)
People who live with stomas suffer impacts in the adaptation process, especially in their reintegration into society. In addition to bodily changes, ostomies can also cause emotional, social, and spiritual imbalances. This is a literature review that aimed to analyze the repercussions identified in the literature related to the perception of ostomy patients on their self-esteem and self-image. Self-esteem involves the perception of body image and senses, the figurations, and mental representations that a person has of others and of himself.  The need for an ostomy causes a series of changes in the patients' self-image, also causing changes in the feeling of self-esteem. In addition, it triggers feelings such as fear, anguish, insecurity, suffering, shame, apprehension, isolation, loss of autonomy, among others. The evaluation of the self-esteem of ostomized individuals is necessary because the patients go through a sudden change in their standard of living, making it essential for the health team involved in the rehabilitation and coping with this new reality, providing a more natural transition possible. DOI:https://doi.org/10.56238/sevened2023.004-054